DISCIPLINARY RESPONSIBILITY OF AN ADVOCATE IN THE REPUBLIC OF UZBEKISTAN: ANALYSIS OF THE LEGISLATION OF NATIONAL AND FOREIGN COUNTRIES - Matmurotov Alibek Ravilovich (Scholar Express Journals, 2023)
This article analyzes the legal documents on the disciplinary responsibility of an advocate, the disciplinary responsibility of an advocate in foreign countries’ legislation on the legal profession, and comments on the possibilities of introducing their positive experience into the national legislation.
Keywords: advocacy; disciplinary responsibility; Disciplinary penalties; admonition